CROVALLEX: Croatian Verb Valence Lexicon - Mikelić Preradović, Nives (Array, 2009)
The goal of this paper is to present CROVALLEX – the first Croatian Verb Valence Lexicon. It contains 1739 verbs with 5118 valence frames. It also contains 173 syntactic-semantic classes (72 classes with two further levels of subdivision). Functional Generative Description (FGD) is used as the background theory for the description of valence frames. Syntactic-semantic classes have been derived from VerbNet and modified for Croatian language. Lexicon has the robust and explicitly defined XML data structure which enables browsing through designated levels. CROVALLEX is available at http://cal.ffzg.hr/crovallex/index.html.